Understanding the Interplay of Perceived Stress, Perceived Social Support and Quality of Life in Pregnant Females : Stress, Support and Pregnancy - Mushtaq, Rabia; Ahmad, Ayesha (Pakistan Journal of Health Sciences, 2024)
The journey of pregnancy or motherhood is transformative, offering fulfillment and joy alongside natural concerns. This phase entails both physiological and emotional shifts, impacting quality of life. Social support enhances the quality of life by improving coping abilities to effectively deal with prenatal stress. Objective: To assess predictive association of perceived stress, perceived social support, and quality of life of pregnant women; and the mediating role of perceived social support in pregnant women's perceived stress and quality of life. Methods: This correlational cross-sectional study was conducted from December-2022 to January-2023 upon 150 pregnant females (x̄-age 26.5 years) selected from gynae OPDs of different hospitals in Karachi, Pakistan through purposive sampling. Urdu versions of Perceived Stress Scale, Multidimensional Scale of Perceived Social Support and the Quality-of-Life questionnaire were used to collect the data. Results: The significant predictive association was found between perceived stress and quality of life (R2= .17, β=-.108, p=<.001), and perceived social support and quality of life of pregnant women (R2=.036, β=-.189, p<.001). Furthermore, Mediation analysis showed that perceived social support partially mediated the association between perceived stress and QoL of pregnant women (R2=.164, F= 15.64, p<.001). Conclusions: It may be concluded that perceived social support positively predicts QOL, while perceived stress negatively predicts QOL in pregnant females. Moreover, PSS mediate the relationship between PS and QOL in this population. Policy making, targeted intervention and support from family, and health practitioners would help reduce the distress level and enhance QoL of pregnant females.